Implementasi Konsep Pertanggungjawaban Pidana Islam dalam Hukum Positif Indonesia - Diana Sri Utami; Siti Hadijah; Cintami Grece Novita Ramadani; Humairah Hannani; M. Rahman Rizki; Zaid Alfauza Marpaung (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Indonesia's positive legal system is not in line with Jinayah's thoughts of accountability. Criminal responsibility according to Islamic criminal law is based on the awareness and intention of the perpetrator (mens rea) and proof of unlawful actions (actus reus), which is in line with sharia principles. The aim of this research is to study how the concept of Islamic criminal responsibility can be applied to Indonesian law by considering the principles of justice, humanity and uniformity in accordance with the country's constitution. The research method used is normative, by looking at various laws in Indonesia and reading literature about Islamic criminal law and its implementation in countries with Islamic law. The research results show that, although there are fundamental differences between Islamic law and Indonesian positive law, several elements of the concept of Islamic criminal responsibility can be exploited, especially in cases containing certain crimes such as qisas, diyat, and ta'zir. By considering Pancasila as the philosophical foundation of the state, these elements can be exploited. It is hoped that this implementation will help strengthen the national legal system by providing space for the religious values ​​that live within it